Deskripsi Gaya Belajar Siswa Kelas IV dan V di SDN 5 Sungai Raya (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the learning styles of students in grades IV and V of SDN 5 Sungai Raya, which focuses on three learning styles, namely (1) visual, (2) auditory, and (3) kinesthetic. The research method used is a qualitative method, while the type of research used is descriptive. The subjects of the study were 12 students in grades IV and V of SDN 5 Sungai Raya, 7 of whom were grade IV students and 5 of whom were grade V students. The techniques used in this study were observation techniques and distribution of questionnaire sheets to students. The focus of the research that the researcher conducted was to describe learning styles including auditory learning styles, visual learning styles, and kinesthetic learning styles in grade IV and V students at SDN 5 Sungai Raya. The results of the study showed that the learning styles of students in grades IV and V of SDN 5 Sungai Raya were different, some had visual learning styles, some had auditory learning styles, some had kinesthetic learning styles, and some had mixed learning styles, namely visual and auditory.